2005
DOI: 10.1159/000085121
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Salmon Calcitonin Nasal Spray Treatment in Postmenopausal Women after Total Hip Arthroplasty

Abstract: Objective: The increasing rate of hip fractures is giving rise to a number of socio-economic problems for the aging community. In addition to being unable to resume their previous living habits, many patients fail to achieve full functional recovery after the fractures. Total hip arthroplasty (THA) is a successful operation for the majority of patients with all forms of hip fractures, being performed increasingly often throughout the world. Revision rates for THA range up to 20% per year. Aseptic loosening is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 80 publications
0
13
0
1
Order By: Relevance
“…However an array of approaches currently exists to improve the pharmacological properties of peptides [56, 57]. For instance, oral insulin formulations already show promising results as treatment of diabetes type 1 [58] and nasal administrations of peptides such as the polypeptide hormone calcitonin [59] have been successfully tested in clinical trials. Hence, further preclinical and clinical development of OSIP108 as a novel therapy for diseases related to excessive apoptosis such as WD or some neurodegenerative diseases, will require considerable efforts in the development of adequate OSIP108 formulations.…”
Section: Discussionmentioning
confidence: 99%
“…However an array of approaches currently exists to improve the pharmacological properties of peptides [56, 57]. For instance, oral insulin formulations already show promising results as treatment of diabetes type 1 [58] and nasal administrations of peptides such as the polypeptide hormone calcitonin [59] have been successfully tested in clinical trials. Hence, further preclinical and clinical development of OSIP108 as a novel therapy for diseases related to excessive apoptosis such as WD or some neurodegenerative diseases, will require considerable efforts in the development of adequate OSIP108 formulations.…”
Section: Discussionmentioning
confidence: 99%
“…23 Calcitonin has also been examined and may be of benefit. 24 Parathyroid hormone is postulated to be of benefit as a result of its effects on bone mass, although this has not been proven. 25 …”
Section: Fractures About Hip Arthroplastymentioning
confidence: 99%
“…There is recent evidence that bisphosphonates (BPs), known to induce macrophage apoptosis, are of potential therapeutic use in the treatment of experimental osteolysis . Rogers et al showed that apoptosis could be induced in the J774 and RAW264 macrophage cell lines by treatment with pamidronate, alendronate, ibandronate, and clodronate.…”
Section: Discussionmentioning
confidence: 99%